2021
DOI: 10.1111/cdev.13545
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Sensitivity and Children’s Cognitive and Socioemotional Outcomes: A Meta‐Analytic Review

Abstract: In a series of meta-analyses, paternal sensitivity was associated with children's (age range: 7 months-9 years) overall cognitive functioning (N = 3,193; k = 23; r = .19), including language skills (k = 9; r = .21), cognitive ability (k = 9; r = .18), and executive function (k = 8; r = .19). Paternal sensitivity was not associated with children's overall socioemotional functioning (N = 2,924; k = 24; r = À.03) or internalizing problems, but it was associated with children's emotion regulation (k = 7; r = .22) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
84
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 99 publications
9
84
1
1
Order By: Relevance
“…Child-reported sense of connectedness to caregivers was a moderate to strong predictor of their COVID-19 depression, anxiety, and happiness. This finding is consistent with a robust body of literature that supports the importance of parental warmth and connection for children’s developmental health outcomes [ 18 21 , 64 ]. Moreover, connection to caregivers may be playing a particularly salient role when access to other traditional supports (e.g., peers, teachers and coaches) is limited or unavailable due to COVID-19 restrictions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Child-reported sense of connectedness to caregivers was a moderate to strong predictor of their COVID-19 depression, anxiety, and happiness. This finding is consistent with a robust body of literature that supports the importance of parental warmth and connection for children’s developmental health outcomes [ 18 21 , 64 ]. Moreover, connection to caregivers may be playing a particularly salient role when access to other traditional supports (e.g., peers, teachers and coaches) is limited or unavailable due to COVID-19 restrictions.…”
Section: Discussionsupporting
confidence: 91%
“…Decades of observational and experimental research has shown that when children feel connected to their caregivers, their developmental health is optimized [ 18 23 ]. However, as children move into the later stages of middle childhood, peer relationships take on more primacy.…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis has also confirmed significant associations between paternal sensitivity and children's executive function and emotional regulation from infancy to childhood (Rodrigues et al, 2021). Children's self-regulatory abilities, a set of skills involved in attention, persistence, motivation, and effortful control, are closely associated with later substance use (Crockett et al, 2006;Fosco et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…In a more recent meta‐analytic review, Rodrigues et al. (2021) found small to moderate associations between paternal sensitivity (defined as “reading the subtle affective and cognitive cues of children and in turn, responding in a manner that is sensitive, stimulating, or both” [p. 554]) and children's better cognitive functioning and emotional regulation, and less externalizing problems. On the other hand, findings on the effects of quantity of father involvement are inconsistent: some showing the quantity of involvement being unrelated to children's well‐being (refer to a meta‐analysis on nonresident fathers; Adamsons & Johnson, 2013) and others showing the quantity being a prerequisite for the quality of involvement (Fabricius et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For a century, studies and theories have been devoted to outline and investigate the maternal impact on the child including risks of maternal psychiatric conditions and the impact of maternal sensitivity on healthy growth of the child. Although past theories regarded the paternal role as essential but complementary to that of the mother, recent studies show specific and substantial effects of fathers on risk versus promotion of child development (Cabrera, 2020;Cabrera et al, 2011;Rodrigues et al, 2021;Volling et al, 2019). However, the paternal role is understudied regarding associations that are less confounded by genetics such as sensitivity towards child development and the impact of paternal depression on the offspring.…”
Section: Introductionmentioning
confidence: 99%